CORRUPTION AS PART OF PROXY WAR: EFFORTS TO ERADICATE THE DANGER OF CORRUPTION IN INDONESIA - Raden Mas Jerry Indrawan (Jurnal Pertahanan & Bela Negara, 2017)
Abstract – Corruption is the main enemy of the nation However, corruption is a totally different battlefield from the regular terminology of war that we understand. This type of war is a war without weapons, without an army and territories. This war is a battle that does not attack with a rifle, but attacking the human conscience with the temptations of materialism. Corruption can harm the development of the Indonesian economy, and impoverishing our people. Corruption resulting in the destruction of the national order in Indonesia, in almost every sectors. That is why the writers considers that corruption is part of a proxy war. Enforcement measures only not enough to combat the corruption, it require preventive action so that these threats will not become an embedded culture. Therefore, the civil defense program may be used as an effective means to eradicate corruption. In this paper, the writers wants to elaborate that corruption is part of a proxy war, and also how the civil defense program could be used to eradicate corruption in Indonesia.Keywords: Corruption, poverty, proxy war, state defense and defending the country